Interpreting a professional biography as an example of applying hermeneutical interpretation (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
The article contains a proposal of application of hermeneutical interpretation in reference to the tradition of biografical interview. The rules of interpretation, being in the world, intersubjectivity, dialogics, the world of everyday life as well as its historical and ligual character have been outlined in the text. The specific categories of research applied to interpretation of a text – especially biographical utterance – were derived from the general rules. The interpretation of a interview with a female movie director made it possible to formulate a conclusion indicating the conditions of entering and performing the profession. The most important among these conditions are: self-reliance, courage in thought and in action, maturity, determination, the ability to establish and maintain relations with collaborators and leading the crew. The extra-subjective categories, such as social change, are important as well.